2014
DOI: 10.4236/ijcm.2014.58064
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Profile and In-Hospital Outcome of Patients with Right Ventricular Myocardial Infarction

Abstract: Objectives: Right ventricular myocardial infarction as assessed by various diagnostic methods accompanies inferior wall myocardial infarction in 30% to 50% of patients. Acute right ventricular myocardial infarction is associated with higher in-hospital morbidity and mortality related to life-threatening hemodynamic compromise and arrhythmias. Since there is scarcity of literature regarding epidemiology of clinical profile as well as in-hospital outcomes of patients with right ventricular myocardial infarction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 24 publications
(20 reference statements)
0
6
0
1
Order By: Relevance
“…18 George et al, found mortality rate to be 12% in patients with inferior wall myocardial infarction and significantly higher at 28% in patients having right ventricular involvement in inferior wall myocardial infarction cases. 21 Memon AG et al, reported more than double in-hospital mortality in RVMI Group as compared to without RVMI. 19…”
Section: Discussionmentioning
confidence: 98%
“…18 George et al, found mortality rate to be 12% in patients with inferior wall myocardial infarction and significantly higher at 28% in patients having right ventricular involvement in inferior wall myocardial infarction cases. 21 Memon AG et al, reported more than double in-hospital mortality in RVMI Group as compared to without RVMI. 19…”
Section: Discussionmentioning
confidence: 98%
“…The present case series is notable for the lack of operative mortality associated with repair of a mechanical complication of an acute inferior wall myocardial infarction. This is a clinically important finding which is highlighted when the outcomes are compared to those from a study by George and colleagues in which acute inferior wall myocardial infarction without mechanical complication resulted in a mortality rate of 12% to 28%, depending on whether there was associated right ventricular involvement . A common cause of death was cardiogenic shock.…”
Section: Discussionmentioning
confidence: 77%
“…Це зумовлює відсутність єдиної думки щодо самостійного впливу ІМ ПШ на підвищення ризику фатальних ускладнень та смерті, що спонукає до подальших досліджень в цьому напрямку. Ряд клінічних випробувань пере-конливо демонструє підвищення числа ускладнень і смертності хворих при бівентрікулярному ІМ в го-строму періоді і віддаленій перспективі в порівнянні з ізольованим ураженням ЛШ [4,5]. Їм суперечать дослідження, які пов'язують високий ризик неспри-ятливого прогнозу не стільки з ІМ ПШ, скільки з поширеністю некрозу ЛШ [6,7].…”
Section: вступunclassified